2022
DOI: 10.7717/peerj.14324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci of agronomic traits in bread wheat using a Pamyati Azieva × Paragon mapping population harvested in three regions of Kazakhstan

Abstract: Background Although genome-wide association studies (GWAS) are an increasingly informative tool in the mining of new quantitative trait loci (QTLs), a classical biparental mapping approach is still a powerful, widely used method to search the unique genetic factors associated with important agronomic traits in bread wheat. Methods In this study, a newly constructed mapping population of Pamyati Azieva (Russian Federation) × Paragon (UK), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
2
0
0
Order By: Relevance
“…Four associations matched the results from studies of the UK reference mapping population Avalon × Cadenza, where QTL associations with HD, PH, and YM2 were identified in the northern, central, and southern regions of Kazakhstan [55]. Another four associations were identical to the genetic positions of QTLs identified in analyses of eight traits using 94 recombinant inbred lines of the mapping population of Pamyati Azieva × Paragon, which were tested in the northern and southern regions of Kazakhstan [56]. Three QTLs (QHD.ta.w.ipbb-2A.2, QHD.ta.w.ipbb-5B.1, and QSMD.ta.w.ipbb-3B) had identical genetic positions to QTLs identified in the GWAS of yield components in a spring wheat collection harvested under two water regimes in northern Kazakhstan [18] (Table S6).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Four associations matched the results from studies of the UK reference mapping population Avalon × Cadenza, where QTL associations with HD, PH, and YM2 were identified in the northern, central, and southern regions of Kazakhstan [55]. Another four associations were identical to the genetic positions of QTLs identified in analyses of eight traits using 94 recombinant inbred lines of the mapping population of Pamyati Azieva × Paragon, which were tested in the northern and southern regions of Kazakhstan [56]. Three QTLs (QHD.ta.w.ipbb-2A.2, QHD.ta.w.ipbb-5B.1, and QSMD.ta.w.ipbb-3B) had identical genetic positions to QTLs identified in the GWAS of yield components in a spring wheat collection harvested under two water regimes in northern Kazakhstan [18] (Table S6).…”
Section: Discussionsupporting
confidence: 70%
“…Notably, the largest number of associations was identified for HD, PH, and NKS, which shows a wide range of variation of these traits in the two regions. The literature survey suggested that 23 of the 173 QTLs identified in our study had also been detected in previous QTL mapping studies and GWAS for HD, SMD, PH, SL, NKS, and YM2 [18,28,[50][51][52][53][54][55][56][57] (Table S6). The majority of these matches were found for PH (nine QTLs), followed by HD (six QTLs) and NKS (four QTLs) (Table S6).…”
Section: Discussionsupporting
confidence: 69%